Teachers’ Communicative Activities in Teaching English as A Foreign Language (Tefl): A Study at Sman 9 Bandar Lampung - Mohammad Muhassin (Bina Nusantara University, 2016)
The research aimed to find out the kinds of communicative activities implemented by English teachers in TEFL at SMAN 9 Bandar Lampung and the dominant communicative activity of each English skill implemented by the teachers. This was a kind of descriptive quantitative research. The technique in collecting data was the direct observation of the English teachers in TEFL at the first, second and third years of SMAN 9 Bandar Lampung. There were three teachers as the sample of the research chosen by using purposive sampling technique. The researcher used the checklist by putting tallies to certain columns. There were 42 items in the checklist of communicative activities implemented by the teachers. The result of the research shows that there are 24 communicative activities implemented by the English teachers at SMAN 9 Bandar Lampung. The research also reveals that the dominant communicative activity of each English skill implemented in TEFL at SMAN 9 Bandar Lampung is teachers’ asking the question in speaking, note-taking in listening, pre-question in reading, and making sentences in writing.